The bitter fruit of American justice: international and domestic resistance to the death penalty - Clarke, Alan W. (Northeastern Univ. Press [u.a.], 2007)
Human rights and the erosion of absolute sovereignty -- Extradition : holding the United States to a higher human rights standard -- Honoring treaty commitments : the Vienna Convention on consular relations -- Death penalty myths : science confronts conventional wisdom -- Attitudes toward capital punishment : do facts matter? -- Executing the innocent -- The moral potency of the innocence argument -- The imperfectability of the system